Encyclopedia of microfluidics and nanofluidics - Li, Dongqing (Springer New York, 2015)
Covering all aspects of transport phenomena on the nano- and micro-scale, the 800 entries include 300 essay entries. The Encyclopedia gives an up to date look at the fundamentals of the field as well as many experiments and applications in growing areas such as energy devices and bioengineering applications.